Exploring the Optoelectronic and Photovoltaic Characteristics of Lead‐Free Cs2TiBr6 Double Perovskite Solar Cells: A DFT and SCAPS‐1D Investigations - M. Khalid Hossain; Sahjahan Islam; M. Najmus Sakib; M. Shihab Uddin; Gazi F. I. Toki; Mirza H. K. Rubel; Jahanara Nasrin; Sara H. Shahatha; M. R. Mohammad; Asma A. Alothman; Chaitany Jayprakash Raorane; Rajesh Haldhar; et al. (Advanced Electronic Materials)
Abstract In recent times, the remarkable advancements achieved in the field of perovskite solar cells (PSCs) have sparked significant research efforts aimed at enhancing their overall performance because of their exceptional optoelectronic properties. Due to the toxicity of lead (Pb), the emergence of Ti‐based (Cs2TiBr6) double‐halide PSCs is regarded as a good alternative to Pb‐based PSCs. Here, density functional theory (DFT) calculations are performed to examine the prospect of Cs2TiBr6 perovskite as a layer of absorber for photovoltaic cells (SCs). These computations looked at the material's structural, optical, and electrical characteristics. The density of states (DOS) results demonstrate strong conductivity, principally provided by the 4p states of Br, whilst Ti‐3d and Cs‐5p orbital electrons offer insignificant contributions. The electronic band structure discloses a direct band gap of 1.534 eV. The covalent connections that exist between Ti and Br atoms and the robust electronic charge density around the Ti atom both demonstrate a significant buildup of electronic charge along the 100 planes. The dielectric function and the coefficient of absorption have significance irrespective of lower energies because it is extremely valuable for solar energy applications. The UV absorption peaks of Cs2TiBr6 have a maximum of ≈15.51 eV and are magnified with photon energy up to 2.46 eV, indicating that it may have potential for solar applications. This work also investigated a good combination of the hole transport layer (HTL) and electron transport layer (ETL) with the Cs2TiBr6 absorber layer. AZnO, Nb2O5, LBSO, and Zn2SnO4 are executed as the ETLs, and MoO3, CuAlO2, MEH‐PPV, ZnTe, CNTS, GaAs, MoS2, PTAA, Cu2Te, Zn3P2 are considered as the HTLs to identify the best HTL/Cs2TiBr6/ETL combinations using the SCAPS‐1D numerical simulation. Among all configurations, ITO/LBSO/Cs2TiBr6/CNTS/Au is examined as the best‐optimized structure of Ti‐based PSC, with JSC of 26.63 mA cm−2, a VOC of 1.123 V, FF of 82.94%, and a power conversion efficiency of 24.82%. To validate the findings, PV parameters like the effect of generation rate, recombination rate, J−V, and Q‐E characteristics are evaluated. The effect of series and shunt resistance and structure working temperature are explored to observe the effect of these on PSC devices. The accomplished outcomes suggest that Cs2TiBr6 can be viewed as an optimistic material for PSCs for its higher stability and environment‐friendly characteristics.